Methemoglobinemia caused by fungicide poisoning: A case report (Bangladesh Critical Care Journal, 2023)
Methemoglobinemia is a potentially fatal condition at a level of more than 70%. It occurs when the ferrous iron inHaemoglobin is oxidized to ferric iron, forming methemoglobin (MetHb), causing decreased capability of hemoglobinto bind and deliver oxygen to tissues. Methemoglobinemia has been linked to a wide array of substances, includingfungicides and industrial chemicals. We describe a patient who developed a high MetHb level of 70.7%, afterdeliberately consuming a fungicide, namely Mancozeb. The "oxygen saturation gap" is the difference between thecalculated oxygen saturation from a standard blood gas machine and the reading from a pulse oximeter. If it is greaterthan 5%, the patient's hemoglobin may be abnormal, representing carbon monoxide poisoning, methemoglobinemia,or sulfhemoglobinemia. Disproportionate cyanosis not responding to supplemental oxygen, chocolate brown blood,and saturation gap of >5% raised the suspicion of methemoglobinemia secondary to ingestion of fungicide. Analternative approach to treatment including intravenous ascorbic acid, NAC, and multiple blood transfusions wasgiven due to the unavailability of methylene blue. A high index of suspicion, early recognition, and an alternativeapproach to management resulted in a favorable outcome.Bangladesh Crit Care J March 2023; 11 (1): 46-50